1999
DOI: 10.1002/(sici)1521-4141(199903)29:03<815::aid-immu815>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of C3b and C5b deposition by CD46 (membrane cofactor protein) after alternative but not classical complement activation

Abstract: C3b and C5b deposition following complement activation, and its regulation by CD46 were studied using xenogenic Chinese hamster ovary (CHO) cells as targets and cytofluorometry. Following activation of the alternative pathway, an initial low level of C3b deposition was observed on CHO cell surfaces after a lag time of approximately 4 min. This was followed by a secondary high level of C3b deposition with a slower rate. C3b deposition was maximal within 15 min. When CD46 was expressed (B2 isoform), the kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 27 publications
6
33
1
Order By: Relevance
“…However, in a preceding study with renal tumor cell lines, we did not find an effect on C3 deposition after blocking of CD46 (Blok et al, 1998). This latter finding was in accordance with prior data suggesting that CD46 is mainly involved in regulation of the alternative pathway (Devaux et al, 1999). However, protection of classical pathway activation by CD46 expression on tumor cell lines has been shown previously (Azuma et al, 1995), although mainly CD55 and CD59 have been implicated as being important for classical pathway activation (Bjørge et al, 1997;Brasoveanu et al, 1996;Cheung et al, 1988); Gorter et al, 1996;Venneker et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…However, in a preceding study with renal tumor cell lines, we did not find an effect on C3 deposition after blocking of CD46 (Blok et al, 1998). This latter finding was in accordance with prior data suggesting that CD46 is mainly involved in regulation of the alternative pathway (Devaux et al, 1999). However, protection of classical pathway activation by CD46 expression on tumor cell lines has been shown previously (Azuma et al, 1995), although mainly CD55 and CD59 have been implicated as being important for classical pathway activation (Bjørge et al, 1997;Brasoveanu et al, 1996;Cheung et al, 1988); Gorter et al, 1996;Venneker et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have examined primarily only one of the four regularly expressed isoforms of MCP (Barilla-LaBarca et al, 2002;Richards et al, 2003).While the MCP isoforms and DAF equivalently and efficiently inhibited the alternative pathway, only DAF inhibited the classical pathway in this experimental system. That MCP preferentially inactivates the alternative pathway agrees with previous findings (Barilla-LaBarca et al, 2002;Devaux et al, 1999;Kojima et al, 1993;Seya and Atkinson, 1989). Interestingly, DAF was also effective in inhibiting the alternative pathway and yet no mutations have thus far linked DAF to aHUS (Esparza-Gordillo et al, 2005) and personal communication, D. Kavanagh).…”
Section: Discussionsupporting
confidence: 86%
“…We have previously shown that MCP minimally inhibits the classical pathway even at low concentrations of Ab (Barilla-LaBarca et al, 2002;Liszewski and Atkinson, 1996). Thus, these findings are consistent with previous studies demonstrating that MCP primarily inhibits the alternative pathway (Devaux et al, 1999;Kojima et al, 1993;Liszewski and Atkinson, 1996). Taken together, these studies indicate that either de novo activation or engagement of the feedback loop is regulated by MCP.…”
Section: Reduced Mcp Expression Decreases Functionalitysupporting
confidence: 93%
See 1 more Smart Citation
“…The cells were washed with PBS and fixed with 4% paraformaldehyde in PBS for 10 min; the cells were permeabilized with 1% Tween 20 in PBS for 10 min. After three washes in PBS, the cells were incubated for 45 min at room temperature with the mouse anti-human C3 ␤-chain Ab WMI (dilution 1/20 in PBS-1% BSA) (28). Following washes, the cells were incubated with goat anti-mouse Ab conjugated with Alexafluor 488 (Invitrogen; dilution 1/100) for 45 min.…”
Section: Immunofluorescence Analysis Of Intracellular C3mentioning
confidence: 99%